Improving the Effectiveness of Education Supervision School Basis, Practice and its strategy - João da Silva; Ibrahim Bafadal; Sunarny Sunarny; Achmad Supriyanto (Green Publisher, 2025)
This study examines the effectiveness of the educational supervision based on school practice and its strategies. The aim of this study is to pinpoint the gap and issues related to the foundational aspects of the existing schools in the area. This research employs qualitative analysis through online library research, paraphrasing, and gathering relevant information from websites and books, as well as various references related to the topic. This information is then analyzed and selected by Turnitin. The findings of this study initially suggest a persuasive strategy that includes an objective for both the sender and the advisor. Secondly, communication serves as a means to reach the goal. Third: the recipient's message must be a matter of free will (i.e., harm from physical threats, and the receiver cannot comply and is typically viewed as coerced rather than persuasive). If that’s the case, persuasive is neither an accident nor coercive. Wholly as connective. There are three categories for the aim of supervision: 1. Academic guidance is offered to assist teachers in enhancing their skills, adopting effective teaching methods, comprehending academic styles, improving classroom approaches, and applying various techniques, among other things. 2. Academic oversight established to oversee and facilitate the teaching and learning process within the school. 3. Academic supervision to support teachers in applying their competencies in fulfilling their responsibilities as educators, to enhance the teachers' own skill levels, and to assist them in instructing students during classroom learning activities.